A hollow visible-light-responsive surface molecularly imprinted polymer for the detection of chlorpyrifos in vegetables and fruits. (1st September 2021) - Chen, Mei-jun; Yang, Hai-lin; Si, Ya-min; Tang, Qian; Chow, Cheuk-fai; Gong, Cheng-bin
Highlights: A surface molecularly imprinted polymer (PS-co-PMAA@VSMIP) was prepared. A hollow structured surface molecularly imprinted polymer (HVSMIP) was prepared. Both PS-co-PMAA@VSMIP and HVSMIP were visible-light-responsive. HVSMIP performed better than PS-co-PMAA@VSMIP for chlorpyrifos analyte. HVSMIP was applied to detect trace chlorpyrifos in spiked apple and carrot samples. Abstract: A visible-light-responsive azobenzene derivative, 3, 5-dichloro-4-((2, 6-dichloro-4-(methacryloyloxy)phenyl)diazenyl)benzoic acid, was synthesized and used as the functional monomer to fabricate a visible-light-responsive core-shell structured surface molecularly imprinted polymer (PS-co-PMAA@VSMIP). After removal of the sacrificial PS-co-PMAA core, a hollow structured surface molecularly imprinted polymer (HVSMIP) was obtained. Both the PS-co-PMAA@VSMIP and HVSMIP were used for the detection of chlorpyrifos, a moderately toxic organophosphate pesticide. They exhibited good visible-light-responsive properties (550 nm for trans→cis and 440 nm for cis→trans isomerization for an azobenzene chromophore) in ethanol/water (9:1, v/v). Compared with the PS-co-PMAA@VSMIP, the HVSMIP had a larger surface area, pore volume, binding capacity, imprinting effect, maximum chemical binding capacity, dissociation constant, and photo-isomerization rate. The HVSMIP was applied to detect trace chlorpyrifos in fruit and vegetable samples. This was achieved by measuring the trans→cis rate constant of the HVSMIP in the sample solution, with good recoveries, low relative standard deviations, and a low detection limit.